The Use of Modern Pedagogical Technologies in Russian Language Lessons - Soliyakhon, Adilova (Journal of Research in Innovative Teaching and Inclusive Learning, 2025)
This study explores the integration of modern pedagogical technologies in Russian language lessons, aiming to enhance student engagement and language proficiency. While traditional teaching methods have long dominated Russian language instruction, there is a growing need to adapt to evolving educational standards and digital advancements. The current literature reflects limited empirical analysis on the effectiveness of modern technologies—such as interactive platforms, gamification, and blended learning—in language acquisition within Russian classrooms. To address this gap, a mixed-methods approach was employed, involving classroom observations, teacher interviews, and student performance assessments across secondary schools. The research focused on the implementation of tools like digital whiteboards, language learning apps, and collaborative online exercises. Findings indicate that the use of these technologies significantly improves student motivation, participation, and retention of linguistic material. Teachers reported greater flexibility in lesson delivery and the ability to tailor content to diverse learning styles. Quantitative data revealed a measurable increase in language performance among students exposed to technology-enhanced lessons compared to control groups taught via traditional methods. The study concludes that modern pedagogical technologies hold substantial promise for revitalizing Russian language education. Their thoughtful integration can not only improve learning outcomes but also align instruction with 21st-century competencies. These findings have broad implications for curriculum developers, educators, and policymakers seeking to modernize language instruction and foster more dynamic classroom environments.